Serum IL-1, Pyroptosis and Intracranial Aneurysm Wall Enhancement: Analysis Integrating Radiology, Serum Cytokines and Histology - Liu, Qingyuan; Zhang, Yisen; Zhu, Chengcheng; Liu, Weiqi; Ma, Xuesheng; Chen, Jingang; Mo, Shaohua; Dong, Linggen; Wang, Nuochuan; Wu, Jun; Liu, Peng; He, Hongwei; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background and purpose: Aneurysm wall enhancement (AWE) is correlated with the rupture and growth risk of unruptured intracranial aneurysms (UIAs). Pyroptosis is a proinflammation mode of lytic cell death, mediated by pyroptosis-related proteins, i.e., gasdermin D and interleukin 1 β (IL-1β). Integrating serum cytokines and histology, this study aimed to investigate the correlation between AWE and pyroptosis in UIAs. Methods: UIA patients receiving microsurgical clipping were prospectively enrolled from January 2017 and June 2020. UIA samples were collected, as well as the corresponding blood samples. In this study, high-resolution magnetic resonance was employed to identify the AWE. The serum 46-cytokines examination and the histological analysis were conducted to determine pyroptosis, CD68 and MMP2. The IL-1 ra/beta ratio was determined by complying with the serum IL-1β and IL-1.ra. A comparison was drawn in the differences between UIAs with and without AWE. Lastly, the correlation between inflammation in UIA samples and serums was investigated. Results: This study included 34 UIA patients. The serum proinflammatory cytokines (IL-1β (P < 0.001) and TNF-α (P < 0.001)) were up-regulated, and serum anti-inflammatory cytokine (IL-1.ra, P = 0.042) were down-regulated in patients with AWE UIAs. The patients with AWE UIAs achieved a higher IL-1ra/beta ratio (P < 0.001). The multivariate logistic analysis demonstrated IL-1β (odds ratio (OR), 1.15; 95% confidence interval (CI), 1.02-1.30; P = 0.028) and IL-1.ra (OR, 0.998; 95% CI, 0.997-1.000; P = 0.017) as the risk factors correlated with the AWE. IL-1ra/beta ratio achieved the highest predictive accuracy (area under the curve (AUC), 0.96) for AWE, followed by IL-1.ra (AUC, 0.90), IL-1β (AUC, 0.88) and TNF-α (AUC, 0.85). As compared with the UIAs without AWE, the AWE UIAs were manifested as a severer wall remodeling, with higher relative levels of pyroptosis-related proteins, CD68 and MMP2. The serum IL-1β, IL-1.ra and IL-1ra/beta ratio had a positive correlation with the relative levels of pyroptosis-related proteins, CD68 and MMP2 in UIA tissues. Conclusion: The serum IL-1β and IL-1.ra were correlated with the AWE. More pyroptosis-related proteins were identified in UIAs with AWE. The serum IL-1β and IL-1.ra were correlated with the pyroptosis-related proteins in aneurysm tissues.